Letters to Lee : From Pearl Harbor to the War's Final Mission - Edmundson, James V. (James Valentine), 1915-2001 (World War II--the global, human, and ethical dimension., 2010)
"In his 36 years of military service, Lt. General James V. Edmundson had over ten thousand hours of pilot time in 137 types of airplanes. In addition to 107 combat missions in World War II, he led 32 combat missions in Korea and 42 in Vietnam. Two years after General Edmundson's death in 2001, his daughter Celia discovered a trunk of his letters and was particularly fascinated with the correspondence between her father and mother, Lee. This very personal story is told through chronological vignettes, letters, and newspaper and magazine articles of the period. The vignettes were written in 2000; the letters begin in 1939 in the beautiful Territory of Hawaii. The two are interwoven and provide detailed descriptions of the conditions both before and after the U.S. entry into the war. Correspondents from the United Press and Newsweek who accompanied Edmundson on combat missions enrich the story. Letters to Lee is a first person account of two of the heroes of World War II and of the love that they shared across the years and miles. They lived their lives with integrity and courage, one example of this great generation and this incredible period in time."--From publisher description.